Persatuan Nelayan Kawasan Kuala Muda (PNKKM) / Muhammad Syafiq Saifurizal - Saifurizal, Muhammad Syafiq (Universiti Teknologi MARA, Sarawak, 2015)
Persatuan Nelayan Kawasan Kuala Muda (PNKKM) is the agency establish that responsible to manage the fishery industry in Malaysia. Besides that, Persatuan Nelayan Kawasan Kuala Muda (PNKKM) was formed to address the emerging needs for a more forward fisherman industry in Malaysia. Persatuan Nelayan was established under Lembaga Kemajuan Ikan Malaysia (LKIM), which has contributed significantly to the development of the fishery industry. The support and administration from Persatuan Nelayan Kawasan Kuala Muda has had bring a lot of impact on the Malaysian fishery industry.